The effects of implicit corrective feedback on production of lexical stress in L2 English - Parlak, Özgür (Studies in Second Language Learning and Teaching, 2024)
The interactionist approach to second language acquisition has yielded a plethora of studies confirming the positive impact of interaction and corrective feedback on second language (L2) development. Nevertheless, only a few studies have attempted to investigate the development of L2 prosody using the interactionist approach. The current study contributes to this line of research by investigating the relationship between recasts and the production of primary stress in L2 English. Following a pretest-posttest design, 68 L1 Arabic speakers were randomly assigned to control and intervention groups. The pre- and posttest comprised sentence-completion and information-exchange tasks, whereas the intervention was a role-play task that dyads carried out with the researcher. The intervention group received a recast upon producing target words with misplaced primary stress, whereas the control group did not receive any corrective feedback. The results of acoustic analyses, which focused on syllable duration, intensity, and pitch, indicated a positive relationship between recasts and development of primary stress placement. The results were also supported by expert listener judgments. The findings suggest that interaction and implicit corrective feedback play a positive role in the development of lexical stress.